ETIKA KEPEDULIAN :: WELAS ASIH DALAM TINDAKAN MORAL - Yeremias Jena (Sekolah Tinggi Agama Islam Sadra, 2014)
Compassion in ethical discourse is used to describe the attitudes and actions of moral agent in helping the vulnerables and the suffering. Discourse around compassion generally focused on whether compassion is an attitude of sympathy or empathy, or it is the attitude of compassion derived from an altruistic attitude which is inherent in intelligent being. This paper argues that compassion is realized only in the context of ethics of care. For that reason, the paper will first distinguish simpaty from empathy and contextualize them within the realm of altruism. At the same time this approach plays the role of criticizing emotive ethics of David Hume and Kantian ethics which is attacked by Kantian ethics as heteronomous.